Review on comparative genome mapping in crop improvement - Zewdu Asrat; Mastewal Gojjam (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Comparative genomics is the study of the similarities and differences in the structure and function of hereditary information across taxa. The objective of this study was to highlight the role of comparative mapping in crop improvement. Hence, the study encompasses comparative genomics over the past two decades, multiple investigations of many additional taxa have delivered two broad messages: multiple investigations of many additional taxa have delivered two broad messages: In most plants, the evolution of the small but essential portion of the genome that actually encodes the organism's genes has proceeded relatively slowly; as a result, taxa that have been reproductively isolated for millions of years have retained recognizable intragenic DNA sequences as well as similar arrangements of genes along the chromosomes. A wide range of factors, such as ancient chromosomal or segmental duplications, mobility of DNA sequences, gene deletion, and localized rearrangements, has been superimposed on the relatively slow tempo of chromosomal evolution. Comparative genomics is the study of the similarities and differences in the structure and function of hereditary information across taxa. The objective of this study was to highlight the role of comparative mapping in crop improvement. Hence, the study encompasses comparative genomics over the past two decades, multiple investigations of many additional taxa have delivered two broad messages: multiple investigations of many additional taxa have delivered two broad messages: In most plants, the evolution of the small but essential portion of the genome that actually encodes the organism's genes has proceeded relatively slowly; as a result, taxa that have been reproductively isolated for millions of years have retained recognizable intragenic DNA sequences as well as similar arrangements of genes along the chromosomes. A wide range of factors, such as ancient chromosomal or segmental duplications, mobility of DNA sequences, gene deletion, and localized rearrangements, has been superimposed on the relatively slow tempo of chromosomal evolution.